Development and validation of the high performance volleyball self-efficacy scale - Machado, T. D. A.; Balaguer, I.; Prado-Gascó, V. J.; Muiños, P.; Lirani, L. D. S.; Arthur, D. P.; Stefanello, J. M. (Perceptual and Motor Skills, 2023)
In this study, we aimed to develop and psychometrically examine a self-efficacy scale for high-performance volleyball athletes. A literature review and interviews with 16 experts led to construction of item content. A preliminary version of the scale was then administered to 24 high-performing adult athletes, followed by administration of the scale to 300 Brazilian high-performing volleyball athletes (M age = 24.88, SD = 5.51 years; 55% male; 45% female). The definitive model contained 19 items, grouped into three factors (Self-Efficacy in the Game, Defensive Self-Efficacy in Volleyball, and Offensive Self-Efficacy in Volleyball). A Global Self-Efficacy score was evaluated through several statistical procedures that provided evidence of an adequate fit of the model to the data, and we showed internal reliability of the item content and invariance of the instrument for both sexes. These results support the instrument`s test content, internal structure, and relation to other variables, indicating that the Volleyball Self-Efficacy Scale (VSES) can now be used to assess the self-efficacy of high performing Brazilian volleyball athletes.